LITERATURE REVIEW ON GENERATION Z’S PERCEPTION OF PRODUCT PURCHASING DECISIONS THROUGH E-COMMERCE FROM THE PERSPECTIVE OF ISLAM BUSINESS ETHICS - Ailatus Sakinah; Hendri Hermawan Adinugraha (IAIN Surakarta, 2022)
Indonesia is currently experiencing rapid technological development, especially in the fields of information technology, communication and media. One of them, e-commerce (Electronic commerce) is a place of trade that utilizes the internet media. The growth of e-commerce in Indonesia is very rapid, as evidenced by the emergence of various kinds of e-commerce. Of the many e-commerce companies that have developed so far, there are still few e-commerce companies that label their companies as companies that obey Islamic law. Therefore, it is still a question whether the transaction process between sellers and buyers in e-commerce is appropriate or violates the norms of Islamic law. This study aims to analyze the perception of Generation Z in making decisions to transact in e-commerce. This research method was qualitative by using the field of literature review. Data collection was done by collecting article sources in the form of journals, previous research and related sources. The results of this study indicate that student perceptions of e-commerce are very good, some e-commerce is in accordance with Islamic law, but some e-commerce is not in accordance with Islamic law. Halal labels on products, systems that run e-commerce, trust, security, service quality, and perceived risk affect product purchasing decisions.